Associative and business models: reflections on the management of football clubs in Brazil (Research, Society and Development, 2022)
The objective of this study is to analyze the management and structure of the business and associative clubs, seeking to identify the strengths and weaknesses of each of them and their viability of success based on documentary research. The study focused on four Brazilian football clubs from the perspective of the legal model and the financial situation from 2010 to 2020. The data analysis allows us to conclude that there is no direct link between the choice of model legal framework implemented in the club and its success. Instead, the critical point for developing a successful management project in clubs lies in the professionalization of management.